Applying Crime Prevention and Health Promotion Frameworks to the Problem of High Incarceration Rates for Aboriginal and Torres Strait Islander Populations: Lessons from a Case Study from Victoria - Battams, Samantha; Delany-Crowe, Toni; Fisher, Matt; Wright, Lester; Krieg, Anthea; McDermott, Dennis; Baum, Fran (The International Indigenous Policy Journal, 2021)
This article examines what kinds of policy reforms are required to reduce incarceration rates of Aboriginal and Torres Strait Islander people through a case study of policy in the Australian state of Victoria. This state provides a good example of a jurisdiction with policies focused upon, and developed in partnership with, Aboriginal communities in Victoria, but which despite this has steadily increasing incarceration rates of Indigenous people. The case study consisted of a qualitative analysis of two key justice sector policies focused upon the Indigenous community in Victoria and interviews with key justice sector staff. Case study results are analysed in terms of primary, secondary, and tertiary crime prevention; the social determinants of Indigenous health; and recommended actions from the Ottawa Charter for Health Promotion. Finally, recommendations are made for future justice sector policies and approaches that may help to reduce the high levels of incarceration of Aboriginal and Torres Strait Islander people.